Discordant performances of non-invasive prenatal testing for foetal trisomy 21 screening in subgroups of pregnancies - Feng Suo; Yi Wang; Na Wang; Yawen Wang; Mingming Liao; Jingjing Wang; Chuanxia Wang; Yan Zhang; Man Zhang; Chu Zhang; Maosheng Gu; Lingshan Gou (Journal of Obstetrics and Gynaecology, 2023)
AbstractBackground Non-invasive prenatal testing (NIPT) has been widely adopted as an approach for foetal aneuploidy screening. This study was to evaluate the performance of NIPT for foetal T21 detection in subgroups of pregnancies and the correlation between Z-score and discordant positive predictive values (PPVs).Methods We retrospectively reviewed the NIPT results among 22361 pregnancies undergoing combined second-trimester screening (cSTS) previously. Sixty-four cases with positive NIPT results for foetal T21 were validated by invasive prenatal diagnosis.Results In pregnancies with cSTS-T21 low-, intermediate-, and high-risk, the PPVs at NIPT were 14.3%, 64.3%, and 86.4%, respectively. Mean Z-scores of positive NIPT cases with cSTS-T21 high- and intermediate-risk were comparable, while were higher than that of cases with pre-test low-risk. Furthermore, PPVs for positive NIPT cases at 3 < Z < 5, 5 ≤ Z < 9, and Z ≥ 9 were 16.7%, 63.2%, and 100.0%, respectively.Conclusions This study suggested that Z-score value of positive cases might be associated with discordant PPVs for T21 screening in subgroups of pregnancies.